2011
DOI: 10.1186/1423-0127-18-76
|View full text |Cite
|
Sign up to set email alerts
|

BACE-1 inhibition prevents the γ-secretase inhibitor evoked Aβ rise in human neuroblastoma SH-SY5Y cells

Abstract: BackgroundAccumulation of amyloid β-peptide (Aβ) in the plaques is one of the major pathological features in Alzheimer's disease (AD). Sequential cleavage of amyloid precursor protein (APP) by β-site APP cleaving enzyme 1 (BACE-1) and γ-secretase results in the formation of Aβ peptides. Preventing Aβ formation is believed to attenuate AD progression and BACE-1 and γ-secretase are thus attractive targets for AD drug development.MethodsCombining BACE-1 and γ-secretase inhibition on Aβ secretion from human neurob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
(34 reference statements)
2
24
0
Order By: Relevance
“…The α-secretase ADAM-10 is known to be associated with exosomes [40,57] and further studies should test if CTF-η inserted in exosomes released by dendrites can give rise to toxic Aη in the synaptic vicinity. Aβ peptides were enriched in exosomes compared to cells, and as expected from previous work [58][59][60], the level of amyloid peptides tended to be higher in APPswe than in APPwt-expressing N2a cells. Accordingly, there was nearly five times more Aβ40 in exosomes from APPswe-than in those of APPwtexpressing N2a (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…The α-secretase ADAM-10 is known to be associated with exosomes [40,57] and further studies should test if CTF-η inserted in exosomes released by dendrites can give rise to toxic Aη in the synaptic vicinity. Aβ peptides were enriched in exosomes compared to cells, and as expected from previous work [58][59][60], the level of amyloid peptides tended to be higher in APPswe than in APPwt-expressing N2a cells. Accordingly, there was nearly five times more Aβ40 in exosomes from APPswe-than in those of APPwtexpressing N2a (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…That γ-secretase inhibition can lead to an increase in the production rate of its Aβ product has been reported in several in vitro and in vivo systems (12, 13, 2123, 27). However, no mechanism has been proposed to explain the origin of this paradoxical behavior by only inhibiting this enzyme.…”
Section: Discussionmentioning
confidence: 77%
“…Here, we demonstrate that the model can quantitatively recapitulate in vitro data. It has been reported that dose-response curves of Aβ 1–40 /Aβ 1–42 against GSIs have two different behaviors depending on the cell type where the compounds are tested (13, 17, 21, 29). For example, it has been shown that in HEK cell lines stably transfected with wild-type APP (HEK APPwt), a biphasic response in the levels of Aβ occurs on treatment with increasing concentrations of GSI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations